1994
DOI: 10.1016/0304-3959(94)90182-1
|View full text |Cite
|
Sign up to set email alerts
|

Histamine-induced modulation of nociceptive responses

Abstract: Because previous studies suggest an antinociceptive role for the neuromodulator histamine (HA) in the periaqueductal grey or the nearby dorsal raphe (PAG/DR), a detailed pharmacological investigation of the effects of intracerebral HA on the hot-plate nociceptive test was performed in rats. Intracerebral microinjections of HA (1 microgram) into the PAG/DR or into the median raphe evoked a mild, reversible antinociceptive response; injections into lateral or dorsal midbrain evoked either a delayed response or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 29 publications
1
37
0
3
Order By: Relevance
“…Histamine, a pain-enhancing substance in the skin and spinal cord (Kajihara et al, 2010), reduces nociceptive transmission when injected directly into the brain (Glick and Crane, 1978;Chung et al, 1984;Bhattacharya and Parmar, 1985;Braga et al, 1992;Sibilia et al, 1992;Malmberg-Aiello et al, 1994;Thoburn et al, 1994). H 1 and H 2 receptors are thought to mediate this effect (Thoburn et al, 1994;Braga et al, 1996;Lamberti et al, 1996).…”
Section: Antinociceptive Profile For Brain Histaminementioning
confidence: 99%
See 2 more Smart Citations
“…Histamine, a pain-enhancing substance in the skin and spinal cord (Kajihara et al, 2010), reduces nociceptive transmission when injected directly into the brain (Glick and Crane, 1978;Chung et al, 1984;Bhattacharya and Parmar, 1985;Braga et al, 1992;Sibilia et al, 1992;Malmberg-Aiello et al, 1994;Thoburn et al, 1994). H 1 and H 2 receptors are thought to mediate this effect (Thoburn et al, 1994;Braga et al, 1996;Lamberti et al, 1996).…”
Section: Antinociceptive Profile For Brain Histaminementioning
confidence: 99%
“…H 1 and H 2 receptors are thought to mediate this effect (Thoburn et al, 1994;Braga et al, 1996;Lamberti et al, 1996). Related to pain relief, H 2 receptors in the brain are activated as part of opioid and nonopioid antinociceptive mechanisms , especially when stress elicits or enhances these responses (Nalwalk and Hough, 1995).…”
Section: Antinociceptive Profile For Brain Histaminementioning
confidence: 99%
See 1 more Smart Citation
“…Intracerebroventricular (ICV) injection of histamine at low doses induces hyperalgesia by acting on presynaptic receptors (H 3 receptors) whereas at high levels it elicits antinociception by acting on postsynaptic receptors (H 1 and H 2 receptors) (Malmberg-Aiello et al 1994;Brown et al 2001). ICV injection of H 1 and H 2 receptor antagonists into the periaqueductal gray has an antinociceptive effect (Thoburn et al 1994). Previously, Mojtahedin et al (2008) reported that ICV pre-treatment with mepyramine (H 1 -receptor antagonist) and famotidine (H 2 -receptor antagonist) prevented histamine-induced antinociception in the formalin test in rats.…”
Section: Discussionmentioning
confidence: 99%
“…O receptor H 2 parece estar envolvido na antinocicepção 9 , enquanto o receptor H 1 está relacionado à ação pró-nociceptiva 8,10 . Antagonistas de receptor H 1 apresentam ação supraespinhal, localizada no núcleo dorsal da rafe ou ao redor da substância cinzenta periaquedutal 11 e atuam em receptores pré-sinápticos 8 . Antagonistas do receptor H 2 como a famotidina e lupitidina apresentaram ações antinociceptivas quando usadas por via sistêmica 12 .…”
Section: Introductionunclassified